GLUCOSE INTOLERANCE IN RELATION TO SOCIOECONOMIC STATUS AND GENDER IN POPULATION OF SRINAGAR CITY - Ahmad, Javid; Shoib, Sheikh; Ashraf, Mohammad; Masoodi, Muneer Ahmad; Ahmad, Rafiq; Rashid, Rauf -ur-; Ahmad, Ashfaq; Bashir, Haamid (Journal of Postgraduate Medical Institute, 2012)
Objective: To assess the pattern of type -2 diabetes in different socioeconomic groups in the urban and peri-urban areas of Srinagar city. Methodology: A detailed questionnaire on the Socioeconomic and Clinical background of the 1040 subjects was collected. After an overnight for blood fasting blood samples were drawn for determination of plasma glucose. Diagnosis of diabetes was based on the American Diabetes Association (ADA 2004). Results: The overall Prevalence of the diabetes in the study population was 6.05% which included 4.03% of known diabetic and 2.02% undiagnosed subjects. There was significant difference between the prevalence of type 2 diabetes in men and women (3.6%vs 8.3% respectively, P=0.0013). Subjects belonging to higher socioeconomic status had greater prevalence of diabetes compared to lower 17.4% vs 3.2% (P<0.001)[middle class (class II & Class III ) versus lower class(Class IV) respectively]. Conclusion: Socioeconomic factors influence the occurrence of diabetes in this study population, with prevalence being more come in the middle Class.